UPAYA PENINGKATAN KINERJA DOSEN BERDASAR ANALISIS BEBAN KERJA DOSEN ( BKD ) DI POLTEKKES KEMENKES SURABAYA - Bambang Giatno Rahardjo; Eny Sayuningsih; Jahja . (JURNAL PENELITIAN KESEHATAN, 2016)
Quality Improvement polytechnic graduates among others influenced by the performance oflecturers. Through BKD (Beban Kinerja  Dosen) is expected to improve the quality of lecturers.Since 2010 BKD has been implemented in Poltekkes throughout Indonesia with the goal ofimproving the performance of the Ministry of Health polytechnic lecturers and the results have notbeen evaluated. This study aimed to identify efforts to improve the performance of lecturers basedon analysis Lecturer Workload. The benefits of this research is to produce recommendationslecturer at improving performance Workload analysis Lecturer (BKD). This study was conducted in 7 Department of the Ministry of Health Surabaya polytechnic.Of the population is 615 lecturers. Sample obtained by random sampling Claster method, a large ofsample 68 respondents. Statistic test using SPSS Linear Regression. The research resulted (1) Individuals who are the most influential factor is the experiencewhile the most uninfluential is the family support. (2) The organization of the most influential factoris the job description, while the most uninfluential is the organizational structure. (3) The mostinfluential factor is the psychology of motivation, while the most uninfluential is the personality. (4)There is a linear relationship between the three factors (individual, organizational, and psychology)to the performance of lecturer (BKD). Keyword : Beban Kinerja Dosen (BKD), Individuals, Organization, Phsycology